BELAJAR MATEMATIKA YANG MENYENANGKAN MELALUI METODE PERMAINAN - Marisa Marisa (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2010)
Mathematics is a boring and difficult subject for many learners. The situation challenges mathematics tutors to look for the solution and to change the learners' perception about mathematics — from a frightening subject to an interesting one. Learning mathematics through games is one of the solutions. Games is a creative method that can help to create a more enjoyable atmosphere for the learners to study mathematics. Games also helps the learners memorize better than that of the other methods because the learners are not only passive listeners but they are more involved in the learning.